Buried modification material for flexible perovskite solar cell and preparation method and application thereof

By using sulfhydryl-containing polymers as buried base modification materials in flexible perovskite solar cells, a 3D cross-linking network of electrostatic interactions and hydrogen bonds is formed, and the defects of perovskite films and insufficient interface binding force are solved. Improves photoelectric efficiency and mechanical stability and extends service life.

CN119264302AActive Publication Date: 2025-01-07NORTHWESTERN POLYTECHNICAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411376098.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-29
Publication Date
2025-01-07
Estimated Expiration
2044-09-29

AI Technical Summary

Technical Problem

During service, flexible perovskite solar cells are easily subjected to stresses such as stretching, shearing, bending, and causing perovskite film to crack and fall off, and their water-oxygen isolation ability is poor. The film prepared at low temperature has a large number of defects, which reduces the Photoelectric efficiency and mechanical stability, the brittleness and interface bonding force of hole transport materials affect their service life.

Method used

Using thiol-containing polymers as buried base modification materials, the polymers generated by cross-linking reactions of polyacrylic acid and its derivatives with thiol-ethylamine to form a 3D cross-linking network of electrostatic interactions and hydrogen bonds, reducing interface defects and enhancing space. The binding force between the hole transport layer and the perovskite layer.

Benefits of technology

It improves the photoelectric efficiency and mechanical stability of flexible perovskite solar cells, enhances interlayer bonding force, extends service life, reduces defects on the oxide surface, and improves the mechanical toughness of the film.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119264302A_ABST
    Figure CN119264302A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of solar cells, in particular to an under-buried modification material for flexible perovskite solar cells and a preparation method and application thereof, polyacrylic acid and derivatives thereof and mercaptoethylamine or analogues thereof are used as main reaction raw materials, and a mercapto-containing polymer under-buried modification material is generated through a cross-linking reaction. And spin-coating the hole transport layer with a buried-bottom modification material to prepare a buried-bottom interface layer, and preparing the flexible perovskite solar cell containing the buried-bottom interface layer based on the buried-bottom interface layer. According to the buried modification material for the flexible perovskite solar cell and the preparation method and application of the buried modification material, the sulfydryl-containing polymer serves as the buried modification material to be applied to a trans-flexible perovskite solar cell, and the efficiency and mechanical stability of the flexible perovskite solar cell are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of solar cells, and in particular to a bottom-embedded modification material for flexible perovskite solar cells, and a preparation method and application thereof. Background Art

[0002] With the continuous innovation of industrial technology, wearable smart devices and portable electronic products have developed rapidly, and the market demand for flexible solar cells is increasing day by day. Metal halide perovskite cells have the advantages of low-temperature processing, thin light-absorbing layer thickness, and lightweight design, which are more advantageous in the preparation of flexible solar cells. At present, the development of flexible perovskite solar cells is very rapid, and the efficiency has increased from 2.62% in 2013 to 25.09% in 2024, 36.50cm 2 The efficiency of flexible photovoltaic modules also reached 18.71%.

[0003] Flexible perovskite solar cells will inevitably be subjected to stresses such as stretching, shearing, and bending during service, which may cause cracking of the perovskite film and interface detachment. The water-oxygen isolation ability of the flexible perovskite substrate is poor, which makes the perovskite light-absorbing layer prone to phase change and decomposition. In addition, flexible substrates are usually not resistant to high temperatures, and there are a large number of defects in the perovskite film prepared at low temperatures, which reduces the photoelectric efficiency and mechanical stability of flexible perovskite solar cells. One of the methods to improve the photoelectric efficiency of flexible perovskite solar cells is to passivate the defects inside and at the interface of the perovskite. Chen Wei's research group (2024, Nature) proposed a buried interface self-assembled single molecule hybridization strategy to induce a more uniform distribution of Me-4PACz molecules. The presence of multi-carboxyl NA monomers effectively improves the wettability of the perovskite solution on Me-4PACz, eliminates the nanopores at the buried interface, enhances the crystallinity of the buried interface of the perovskite, and reduces the concentration of buried interface defects, thereby obtaining a high-efficiency perovskite solar cell. Zhang Weifeng's group (2024, Advanced Materials) used two new donor-acceptor semiconductor covalent organic frameworks (COFs) as modified materials for the buried interface of inverse perovskite solar cells. These COFs effectively regulated the morphology and defects of the buried interface film, and better matched the energy level of the perovskite film, thereby improving the extraction and transfer of interfacial charges. Tan Zhan'ao's group (2023, Advanced Materials) designed an amphoteric organic salt, 2-(4-fluorophenyl)ethylammonium-4-methylbenzenesulfonate (4FPEAPSA) to optimize the film morphology and energy level arrangement of the buried interface of the perovskite, passivate the defects of iodine and formamidine vacancies, and restore the Fermi level of the perovskite to a defect-free state.

[0004] The above methods have effectively improved the photoelectric efficiency and stability of perovskite solar cells, but nickel oxide, a hole transport material commonly used in trans perovskite solar cells, is an inorganic material that is inherently brittle. In addition, the bottom interface bonding between the hole transport layer and the perovskite layer is not strong enough, which can easily lead to interface cracking, thereby reducing the service life of the trans flexible perovskite solar cells during service, hindering the development of the industrialization of flexible perovskite solar cells. Summary of the invention

[0005] The purpose of the present invention is to provide a bottom buried modification material for flexible perovskite solar cells, a preparation method and an application thereof, by introducing a thiol-containing polymer bottom buried modification material, passivating the defects of the bottom buried interface, enhancing the interface bonding force between the hole transport layer and the perovskite layer, thereby improving the efficiency and mechanical stability of the inverted flexible perovskite solar cell.

[0006] To achieve the above-mentioned purpose, the present invention provides a bottom buried modification material for flexible perovskite solar cells, which uses polyacrylic acid and its derivatives and mercaptoethylamine or its analogs as main reaction raw materials to generate a mercapto-containing polymer bottom buried modification material through a cross-linking reaction.

[0007] Preferably, the polyacrylic acid and its derivatives are one of polyacrylic acid, polymethacrylic acid, sodium polyacrylate and potassium polyacrylate.

[0008] Preferably, the mercaptoethylamine or its analogue is one of mercaptoethylamine, mercaptopropylamine and mercaptobutylamine.

[0009] The above-mentioned method for preparing a bottom buried modification material for a flexible perovskite solar cell comprises the following steps:

[0010] S1, dissolving polyacrylic acid and its derivatives in solvent one to prepare reaction solution one;

[0011] S2, dissolving mercaptoethylamine or its analogue in solvent 2 to prepare reaction solution 2;

[0012] S3. Use a dropper to draw a drop of the reaction solution 2 of S2 and add it to the reaction solution 1 of S1. After the reaction is complete, wash the reaction product with an alcohol solution, vacuum dry it, and store it in a nitrogen environment to obtain a thiol-containing polymer buried modification material.

[0013] Preferably, the solvent one in S1 is one of water, methanol, ethanol, propanol or a mixed solution of methanol and water, and the concentration of the reaction solution one is 25-40 mg / mL.

[0014] Preferably, the second solvent in S2 is one of water, methanol, ethanol and isopropanol, and the concentration of the second reaction solution is 10-20 wt %.

[0015] Preferably, the alcohol solution in S3 is a methanol solution.

[0016] The above-mentioned application of the bottom buried modification material for flexible perovskite solar cells is applied to the preparation of flexible perovskite solar cells, comprising the following steps:

[0017] T1. Pretreatment of flexible substrate;

[0018] T2, preparing a hole transport layer on the flexible substrate of T1;

[0019] T3, preparing a buried interface layer on the hole transport layer of T2;

[0020] T4, preparing a perovskite layer on the buried interface layer of T3;

[0021] T5, depositing an electron transport layer on the perovskite layer of T4;

[0022] T6. Depositing a metal electrode on the electron transport layer of T5.

[0023] Preferably, the flexible substrate in T1 is polyethylene naphthalate / indium tin oxide or polyethylene terephthalate / indium tin oxide.

[0024] Preferably, the material of the hole transport layer in T2 is nickel oxide, PEDOT:PSS, PTAA or SAM monolayer.

[0025] Preferably, the preparation method of the buried interface layer in T3 is to dissolve the buried bottom modification material in deionized water to obtain a buried bottom modification material solution, spin-coat the buried bottom modification material solution on the wet film of the hole transport layer, the spin-coating speed is 1500-5000 rpm, the spin-coating time is 15-40 s, and after spin-coating, annealing is performed at 100-150°C for 10 min-30 min, and the concentration of the buried bottom modification material solution is 0.01-5 mg / mL.

[0026] Preferably, the perovskite layer in T4 is an APbX3 structure, wherein A is one or a mixture of methylamine, formamidine, and cesium ion, and X is one or a mixture of I, Br, and Cl.

[0027] Preferably, the metal electrode in T6 is one of gold, silver and copper, and the thickness of the metal electrode is 50 to 300 nm.

[0028] Mechanism of the present invention:

[0029] The bottom buried modification material provided by the present invention can be - 、-NH 3+The electrostatic interaction and hydrogen bonding between the -SH functional groups form a strong 3D cross-linked network, which can serve as a buffer layer between the hole transport layer and the perovskite film, reducing the interlayer force of the flexible perovskite solar cell; the C=O in the polymer can reduce the defects on the oxide surface and improve the mechanical toughness of the hole transport layer through chemical coordination. The -SH in the polymer can form a stable chemical bond with the lead ions suspended on the perovskite surface, reduce the defect state density on the perovskite surface, and passivate the defects of the perovskite film. This type of thiol-containing polymer buried modification material can passivate interface defects and improve interface strength, thereby obtaining an efficient and stable flexible perovskite solar cell.

[0030] Beneficial effects of the present invention:

[0031] (1) The preparation method of the buried modification material for flexible perovskite solar cells of the present invention is simple, the raw materials are cheap and easy to obtain, and the experimental repeatability is strong, which meets the requirements of low-temperature preparation of flexible perovskite solar cells;

[0032] (2) The buried modification material for flexible perovskite solar cells of the present invention is constructed into a 3D cross-linked network through hydrogen bonding and electrostatic interaction. The 3D cross-linked network is introduced between the hole transport layer and the perovskite film as a buffer layer, which can reduce the Young's modulus of the hole transport layer and the perovskite film and enhance the interlayer bonding force;

[0033] (3) The present invention is used for the bottom modification material of flexible perovskite solar cells. The carboxylic acid group and the thiol group of the terminal group can synergistically passivate defects, improve the quality of the hole transport layer and the perovskite film, and further enhance the photoelectric performance and mechanical durability of the flexible perovskite solar cell.

[0034] The technical solution of the present invention is further described in detail below through the accompanying drawings and embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a schematic diagram of the structure of a transverse flexible perovskite solar cell with a buried interface according to the present invention;

[0036] Figure 2 This is a comparison chart of Young's modulus obtained by testing the nickel oxide hole transport layer of Example 2 of the present invention and Comparative Example 1;

[0037] Figure 3 A comparison diagram of the cross-sectional morphology of the perovskite layer of the perovskite solar cell prepared in Example 2 of the present invention and Comparative Example 1;

[0038] Figure 4 A comparison chart of Young's modulus of perovskite films prepared in Example 2 of the present invention and Comparative Example 1;

[0039] Figure 5This is a comparison chart of mechanical bending stability test results of flexible perovskite solar cells prepared in Example 2 of the present invention and Comparative Example 1;

[0040] Figure 6 A comparison diagram of JV curves of the flexible perovskite solar cells prepared in Example 2 of the present invention and Comparative Example 1;

[0041] Figure 7 This is a JV curve diagram of the flexible perovskite solar cell prepared in Example 3 of the present invention;

[0042] Figure 8 This is a JV curve diagram of the flexible perovskite solar cell prepared in Example 4 of the present invention. DETAILED DESCRIPTION

[0043] The present invention is further described below in conjunction with the accompanying drawings and embodiments. Unless otherwise defined, the technical terms or scientific terms used in the present invention should be the common meanings understood by people with ordinary skills in the field to which the present invention belongs. The above-mentioned features or features mentioned in the specific examples mentioned in the present invention can be combined arbitrarily, and these specific embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention.

[0044] Example 1

[0045] The present invention provides a bottom-embedded modification material for a flexible perovskite solar cell, which uses polyacrylic acid (PAA) and mercaptoethylamine (MEA) as reaction raw materials to react and generate polymer mercaptoethylamine polyacrylate (PAA-MEA), and the preparation method thereof specifically includes the following steps:

[0046] S1. Preparation of polyacrylic acid solution

[0047] 1.09 g of PAA was added into a round-bottom flask containing 30 mL of methanol solvent, and stirred with a magnetic bar until it was completely dissolved to obtain a polyacrylic acid solution;

[0048] S2. Preparation of mercaptoethylamine solution

[0049] Dissolve mercaptoethylamine in methanol solvent to prepare 10 mL of mercaptoethylamine solution with a concentration of 11 wt %;

[0050] S3. Use a dropper to draw the mercaptoethylamine solution of S2 and slowly add it dropwise to the polyacrylic acid solution of S1. After the reaction is complete, filter and collect the crude product with filter paper, wash the crude product three times with methanol solution, put the washed product into a vacuum drying cabinet, and vacuum dry it at 50°C for 12 h to obtain PAA-MEA polymer material as a bottom modification material. Put the dried solid PAA-MEA polymer into a small bottle and put it into a nitrogen glove box for storage.

[0051] Example 2

[0052] Figure 1 The schematic diagram of the structure of the inverted flexible perovskite solar cell with a buried interface of the present invention is as follows Figure 1 As shown, a bottom-embedded modification material for a flexible perovskite solar cell provided by the present invention is applied to prepare a flexible perovskite solar cell, comprising the following steps:

[0053] T1. Pretreatment of flexible substrates

[0054] T1.1. PET / ITO was selected as the flexible substrate, and it was cut into 1.5 cm × 1.5 cm size with a paper cutter according to the etching line. The flexible substrate was ultrasonically cleaned in the order of deionized water, detergent, and ethanol. After cleaning, the flexible substrate was placed in a drying cabinet and dried at 70°C for 1 hour.

[0055] T1.2. Cut the glass slide into 1.5cm×1.5cm size, stick high temperature resistant double-sided tape on all sides, stick the dried flexible substrate on the cut glass slide, treat with UV-ozone for 15min, and then plasma clean for 60s for use.

[0056] T2. Preparation of hole transport layer on the flexible substrate of T1

[0057] T2.1. Weigh 15 mg of nickel oxide and add 1 mL of deionized water. Place in an ultrasonic machine for 40 min to obtain a nickel oxide dispersion with a concentration of 15 mg / mL.

[0058] T2.2. Spin-coat the nickel oxide dispersion on the flexible substrate treated in T1 at a speed of 3000 rpm for 25 s. After the spin coating, annealing is not performed to obtain a wet film of the hole transport layer.

[0059] T3. Prepare a buried interface layer on the hole transport layer of T2

[0060] T3.1. Weigh 2 mg of PAA-MEA product and add 20 mL of deionized water to prepare a uniform solution to obtain a PAA-MEA solution with a concentration of 0.1 mg / mL. Place the solution in an ultrasonic machine for ultrasonic treatment for 20 min.

[0061] T3.2. Spin-coat the PAA-MEA solution on the unannealed hole transport layer wet film at a speed of 5000 rpm for 30 seconds. After the spin coating is completed, anneal at 100°C for 20 minutes to obtain a nickel oxide hole transport layer after the buried interface layer is treated, and then put it into a nitrogen glove box for use.

[0062] T4. Preparation of perovskite layer on the buried interface layer of T3

[0063] T4.1 with Cs0.05 FA 0.85 MA 0.1 PbI 3 As a light absorbing material for the perovskite layer, the light absorbing material is dissolved in a solvent to prepare a perovskite solution with a concentration of 1.5 mol / mL, and the solvent is a mixed solvent of N,N-dimethylformamide (DMF) and dimethyl sulfoxide (DMSO) in a volume ratio of 4:1;

[0064] T4.2 The perovskite solution is spin-coated on the buried interface layer by a multi-step spin coating method. The first step of spin coating is to spin coat at a speed of 1000 rpm for 10 seconds, and the second step of spin coating is to spin coat at a speed of 5000 rpm for 30 seconds. In the second step, anti-solvent chlorobenzene (CB) is added dropwise at the 12th second of the spin coating. After the spin coating is completed, annealing is performed at 100°C for 50 minutes to form a perovskite layer.

[0065] T5. Depositing an electron transport layer on the perovskite layer of T4

[0066] The electron transport layer C60 and BCP were vacuum evaporated on the perovskite layer. The substrate with the perovskite layer prepared by T4 was placed in the evaporation mask. -4 At pa, C60 was started to be evaporated, and the thickness of the C60 layer was 25nm. Then, when the chamber temperature dropped below 260℃, BCP was started to be evaporated, and the thickness of the BCP layer was 5nm.

[0067] T6. Depositing metal electrodes on the electron transport layer of T5

[0068] Place the substrate after T5 electron transport layer deposition in the mask, install the silver boat, place 2 silver particles, close the hatch, set the material parameters, set the evaporation rate to 0.01nm / s, and the final thickness to 120nm. First, roughly pump until the pressure drops below 5Pa, then finely pump until the pressure drops to 10 -4 pa, pre-evaporation can be started, and after the rate is stable, evaporation can be officially started. After the evaporation is completed, the substrate is taken out and stored in a nitrogen glove box to obtain an inverted flexible perovskite solar cell with a buried interface layer.

[0069] Example 3

[0070] Taking Example 2 as a benchmark, the difference from Example 2 is that the concentration of the PAA-MEA solution in T3.1 is 0.01 mg / mL.

[0071] Example 4

[0072] Taking Example 2 as a benchmark, the difference from Example 2 is that the concentration of the PAA-MEA solution in T3.1 is 1 mg / mL.

[0073] Comparative Example 1

[0074] The difference compared with Example 2 is that step T3 is not performed, that is, the buried interface layer is not prepared, and only the nickel oxide dispersion is spin-coated on the flexible substrate to obtain a nickel oxide hole transport layer without a buried interface layer, and then a flexible perovskite solar cell without a buried interface layer is obtained.

[0075] Performance Testing

[0076] The nickel oxide hole transport layer after the buried interface layer treatment prepared in Example 2 and the nickel oxide hole transport layer without the buried interface layer prepared in Comparative Example 1 were subjected to nanoindentation tests respectively. The results are as follows: Figure 2 As shown, the Young's modulus of Example 2 is significantly lower than that of Comparative Example 1, which means that the nickel oxide hole transport layer after PAA-MEA buried interface modification is more flexible and plastic, and the film is not prone to cracks or breaks when subjected to stress.

[0077] The perovskite layers of the flexible perovskite solar cells prepared in Example 2 and Comparative Example 1 were analyzed by cross-section scanning electron microscope (SEM) respectively, and the morphology was as follows: Figure 3 As shown, the perovskite grains of Example 2 are arranged more orderly and have higher quality. The neat arrangement of the grains can reduce defects at the grain boundaries and reduce the probability of non-radiative recombination, thereby improving the photoelectric performance of the perovskite solar cell.

[0078] The perovskite layers of the flexible perovskite solar cells prepared in Example 2 and Comparative Example 1 were subjected to nanoindentation tests, respectively. The results are as follows: Figure 4 As shown, the Young's modulus of Example 2 is significantly reduced compared with that of Comparative Example 1. The reduction of Young's modulus increases the reliability and stability of the perovskite solar cell during service.

[0079] The flexible perovskite solar cells prepared in Example 2 and Comparative Example 1 were subjected to a 3 mm mechanical bending test, and the efficiency of the cells was recorded every 1000 bends. The results are as follows: Figure 5 As shown, it is indicated that the buried interface treatment method provided by the present invention can improve the mechanical stability of flexible perovskite solar cells.

[0080] The flexible perovskite solar cells prepared in Example 2 and Comparative Example 1 were respectively subjected to AM 1.5G, 100 mW cm -2 The photoelectric performance test was carried out under the lighting conditions of Figure 6 As shown, the efficiency of comparative example 1 is 19.08%, and the efficiency of example 2 is 22.05%, indicating that the buried interface treatment method provided by the present invention can improve the efficiency of flexible perovskite solar cells.

[0081] The flexible perovskite solar cell prepared in Example 3 was tested under AM 1.5G, 100 mW cm -2 The photoelectric performance test was carried out under the lighting conditions of Figure 7 As shown, the obtained efficiency is 19.68%.

[0082] The flexible perovskite solar cell prepared in Example 4 was tested under AM 1.5G, 100 mW cm -2 The photoelectric performance test was carried out under the lighting conditions of Figure 8 As shown, the obtained efficiency is 20.33%.

[0083] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that they can still modify or replace the technical solution of the present invention with equivalents, and these modifications or equivalent replacements cannot cause the modified technical solution to deviate from the spirit and scope of the technical solution of the present invention.

Claims

1. A bottom-embedded modification material for flexible perovskite solar cells, characterized in that: Polyacrylic acid and its derivatives and mercaptoethylamine or its analogs are used as main reaction raw materials to generate a polymer bottom-burying modification material containing mercapto groups through a cross-linking reaction.

2. The bottom buried modification material for flexible perovskite solar cells according to claim 1, characterized in that: Polyacrylic acid and its derivatives are one of polyacrylic acid, polymethacrylic acid, sodium polyacrylate and potassium polyacrylate.

3. The bottom buried modification material for flexible perovskite solar cells according to claim 1, characterized in that: The mercaptoethylamine or its analogue is one of mercaptoethylamine, mercaptopropylamine and mercaptobutylamine.

4. A method for preparing a bottom-embedded modification material for a flexible perovskite solar cell according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1, dissolving polyacrylic acid and its derivatives in solvent one to prepare reaction solution one; S2, dissolving mercaptoethylamine or its analogue in solvent 2 to prepare reaction solution 2; S3. Use a dropper to draw a drop of the reaction solution 2 of S2 and add it to the reaction solution 1 of S1. After the reaction is complete, wash the reaction product with an alcohol solution, vacuum dry it, and store it in a nitrogen environment to obtain a thiol-containing polymer buried modification material.

5. The method for preparing a bottom buried modification material according to claim 4, characterized in that: The solvent 1 in S1 is one of water, methanol, ethanol, propanol or a mixed solution of methanol and water, and the concentration of the reaction solution 1 is 25-40 mg / mL.

6. The method for preparing a bottom buried modification material according to claim 4, characterized in that: The second solvent in S2 is one of water, methanol, ethanol and isopropanol, and the concentration of the second reaction solution is 10-20 wt %.

7. An application of the bottom-embedded modification material for flexible perovskite solar cells according to any one of claims 1 to 3, characterized in that: The method is applied to prepare a flexible perovskite solar cell, comprising the following steps: T1. Pretreatment of flexible substrate; T2, preparing a hole transport layer on the flexible substrate of T1; T3, preparing a buried interface layer on the hole transport layer of T2; T4, preparing a perovskite layer on the buried interface layer of T3; T5, depositing an electron transport layer on the perovskite layer of T4; T6. Depositing a metal electrode on the electron transport layer of T5.

8. The use of a bottom-embedded modification material for a flexible perovskite solar cell according to claim 7, characterized in that: The flexible substrate in T1 is polyethylene naphthalate / indium tin oxide or polyethylene terephthalate / indium tin oxide.

9. The use of a bottom-embedded modification material for a flexible perovskite solar cell according to claim 7, characterized in that: The material of the hole transport layer in T2 is nickel oxide, PEDOT:PSS, PTAA or SAM monolayer.

10. The use of a bottom-embedded modification material for a flexible perovskite solar cell according to claim 7, characterized in that: The preparation method of the buried interface layer in T3 is to dissolve the buried modification material in deionized water to obtain a buried modification material solution, spin-coat the buried modification material solution on the wet film of the hole transport layer, the spin-coating speed is 1500-5000 rpm, the spin-coating time is 15-40s, and after spin-coating, annealing is performed at 100-150°C for 10min-30min. The concentration of the buried modification material solution is 0.01-5mg / mL.

Citation Information

Patent Citations

  • Water-soluble quantum dot and preparation method thereof

    CN109306264A

  • Interface modification molecule applied to lead-based perovskite solar cell

    CN114805150A

  • Perovskite solar cell and preparation method thereof

    CN115117247A

  • Perovskite solar cell and preparation method thereof

    CN115942842A

  • Memory device and operating method thereof

    KR1020240077034A